Socio-economic and Demographic Factors of Excess Mortality Due to the Coronavirus Pandemic in Regions of Russia - Mikhail A. Maximov; Nikita V. Migunov (Население и экономика)
This paper examines the factors associated with excess mortality in Russian regions during the coronavirus pandemic, analyzing them separately for different waves of the pandemic. The study utilizes data from 85 Russian regions on excess mortality – calculated as the number of deaths in each month exceeding the expected number based on the trend of the previous four years – along with socio-economic characteristics (income, unemployment, inequality, migration), vaccination rates, healthcare system characteristics, and the self-isolation index. The analyzed period spans from April 2020 to February 2022. Based on these data, panel regressions with fixed effects and OLS models of accumulated mortality were constructed separately for the second wave (September 2020 – February 2021) and the third wave (July 2021 – February 2022) of the pandemic. The key findings indicate that in both the second and third waves, there was a positive relationship between excess mortality and average per capita income. Only in the second wave was a positive relationship observed between excess mortality and the level of self-isolation, the number of doctors per capita, and migration, while a negative relationship was found with unemployment. In contrast, only in the third wave was there a negative relationship between excess mortality and vaccination rates, migration, unemployment, and the number of hospital beds per capita.